Capacity Building for Inclusive Schools: Empowering Teachers and Parents in Child-Friendly Education - hasbiyallah Hasbiyallah; Karman Karman; Heri Khoiruddin; Mahlil Nurul Ihsan (Communautaire: Journal of Community Service, 2026)
This study aims to analyze the effectiveness of community empowerment initiatives in strengthening inclusive, child-friendly, and disability-responsive early childhood education environments. The research focuses on how structured teacher and parent training can improve pedagogical competence, increase awareness of children with diverse learning needs, and strengthen collaboration between school and home. A mixed-methods approach was used, combining quantitative assessments of participants' knowledge and attitudes with qualitative data from observations, reflections, and stakeholder feedback. The results indicate that targeted empowerment programs contributed to positive changes in teachers' ability to adapt learning strategies, parents' understanding of inclusive support at home, and the development of a more collaborative school culture. Participants showed improved awareness that inclusion is not limited to physical access but also requires emotional, instructional, and social support. This study implies that sustainable inclusive education requires continuous training, active parental participation, and institutional commitment to create responsive learning ecosystems where every child can participate meaningfully.